Characteristic of Wheat Flour Nuggets : Study of Cooking Process and Proportion of Red Beans - Marina Revitriani; Diana Puspitasari; Fungki Sri Rejeki (Universitas Dr Soetomo, 2022)
Making nuggets by replacing meat with red beans can be used as a variant of nuggets for vegetarian consumption. Red beans have hard skin, so it is necessary to know the most appropriate cooking method to produce quality nuggets. The use of whole wheat flour as a binder aims to increase the fiber and protein content of the product. The purpose of this study was to determine the proportion of red beans and whole wheat flour as well as to show how to cook red beans for the quality of the nugget produced. This study used a factorial randomized block design (RAK) the first factor was the proportion of red beans and wheat flour (K), namely K1 (60%:40%), K2 (50%:50%), K3 (40%:60%). The second factor was the red beans cooking process (P), namely P1 (boiling) and P2 (steaming). The results showed that there was no interaction in all treatments. The treatment of the proportion of red beans and whole wheat flour had no significant effect on all parameters, while the treatment of red bean cooking affected the parameters of water content, ash, and carbohydrates. The results of the organoleptic test had a significant effect on taste, aroma, texture, and color. K3P2 treatment (proportion of red beans: 40%: 60% whole wheat flour and steaming) became the selected treatment with parameters water content 49.09%, ash content 1.85%, protein content 10.62 %, fat content 2.90%, carbohydrate content 35.53% and total preference for taste 63.3%, aroma 53.3%, texture 43.3% and color 63.4%.